Sex-specific growth arrest in a lizard - Kubička, Lukáš; Tureček, Adam; Kučera, Tomáš; Kratochvíl, Lukáš (iScience, 2022)
(1) In contrast to mammals and birds, reptiles have been considered as indeterminate growers, whose growth reflects differential allocation of resources to growth versus other energetically demanding processes such as reproduction. (2) We monitored the growth and activity of bone growth plates, hormonal profiles, and reproductive activity in males and females of the male-larger gecko Paroedura picta. We show that growth plates fuse in this species in a sex-specific manner. The more abrupt epiphyseal closure and more pronounced growth deceleration in females coincide with the increased activity of their reproductive organs. (3) We conclude that at least some lizards are determinate growers whose sexual size dimorphism is potentially driven by ovarian hormones. The major difference in growth between endothermic and ectothermic amniotes appears to be in the magnitude of growth before and after the first reproduction, not in the mechanistic processes such as senescence of growth plate cells.
Keywords: Evolutionary biology; Zoology; Ichthyology; Evolutionary developmental biology